The Bank Concentration and Risk Exposure: Empirical Insights from Asian Countries - Budhathoki, Prem Bahadur; Bhattarai, Ganesh; Aryal, Narayan Prasad; Ghimire, Shiva Raj (Nepal Journal of Multidisciplinary Research, 2024)
Background: The relationship between bank rivalry and stability is a subject of discussion in both theoretical and empirical research. The two competing theories, the (1) competition-stability and (2) competition-fragility theories, provide an alternate explanations, leading to controversy over the merger and acquisition policies implemented by Asian governments. This study examines the influence of bank rivalry, profitability, diversity, efficiency, and liquidity on bank stability in Asian countries. Methods: This study used annual data from 11 Asian countries spanning 14 years (2007-2020) and comprising 154 observations. The secondary data were extracted from the Global Financial Development Database (2023). The unit root test, cointegration test, and random effect model were the main methods employed in this work to assess stationarity, long-term relationships, and the influence of bank competition on stability in Asian nations, respectively. Results: The findings revealed that the bank concentration ratio (β = 1.975, p < .01) and cost-to-income ratio (β = -.375, p < .01) negatively affect bank stability, while the noninterest income-to-total income ratio (β = .180, p < .05), credit-to-deposit ratio (β = .346, p < .01), liquid assets-to-deposit ratio (β = .087, p < .05), and net interest margin (β = .036, p < .05) positively affect bank stability in Asian countries. Conclusion: This study concludes that bank competition and efficiency negatively affect bank stability, while income diversification, profitability, and liquidity positively affect bank stability in Asian countries. Novelty: Using a more recent dataset, this study analyzes the effects of competition on stability through cross-country analysis. This also offers extensive literature on the Asian context.